Blended Learning Model in Partnership of PAUD Institution With Family Through Parenting Class in Developing The Potential of Early Children - Putri, Lili Dasa; Kamil, Mustofa; Hatimah, Ihat; S. Ardiwinata, Jajat (Universitas Negeri Padang, 2023)
Development of a partnership model for PAUD institutions with families in developing the potential of early childhood. The model development carried out is a blended learning-based partnership. The purpose of this study was to develop a partnership model for PAUD institutions and families in developing the potential of early childhood based on blended learning to increase the knowledge, attitudes and skills of parents in developing the potential of children according to their age. PAUD institution partnerships with families are carried out in the form of parenting classes. Partnerships are carried out using online (online) and offline (offline) strategies. In this study, researchers used the Research and Development (R&D) method through preliminary study stages by observing, developing media designs, validating, limited trials, media revisions, wider trials. Sources of data from this study included parents, PAUD educators and PAUD managers. The results of the study show that the partnership model for PAUD institutions and families based on blended learning is effective in increasing the knowledge, attitude, and skills of parents in developing the potential of early childhood. This decision was based on the results of data analysis using the T-test using SPSS which concluded that the data taken had significant differences between the pretest and posttest. The results of this study become recommendations in developing partnership programs that can be applied to other PAUD institutions.